Explication of the Potential of 2-Hydroxy-4-Methoxybenzaldehyde in Hampering Uropathogenic Proteus mirabilis Crystalline Biofilm and Virulence - Durgadevi, Ravindran; Abirami, Gurusamy; Alexpandi, Rajaiah; Nandhini, Kumar; Kumar, Ponnuchamy; Prakash, Santhiyagu; Veera Ravi, Arumugam (Frontiers in Microbiology, 2019)
P. mirabilis is an important etiological agent of catheter-associated urinary tract infections (CAUTIs) owing to its efficient crystalline biofilm formation and virulence enzyme production. Hence, the present study explicated the antibiofilm and antivirulence efficacy of 2-hydroxy-4-methoxy benzaldehyde (HMB) against P. mirabilis in a non-bactericidal manner. HMB showed concentration-dependent biofilm inhibition, which was also evinced in light, confocal and scanning electron microscopic analyses. The other virulence factors such as urease, hemolysin, siderophores, and extracellular polymeric substances production as well as swimming and swarming motility were also inhibited by HMB treatment. Further, HMB treatment effectively reduced the struvite/apatite production as well as crystalline biofilm formation by P. mirabilis. Furthermore, the results of gene expression analysis unveiled the ability of HMB to impair the expression level of virulence genes such as flhB, flhD, rsbA, speA, ureR, hpmA and hpmB, which was found to be in correlation with the results of in vitro bioassays. Additionally, the cytotoxicity analysis divulged the innocuous characteristic of HMB against human embryonic kidney cells. Thus, the present study reports the potency of HMB to act as a promising therapeutic remedy for P. mirabilis instigated CAUTIs.